Poligami dalam Hukum Islam Indonesia (Analisis Terhadap Putusan Pengadilan Agama No. 915/ pdt.g/ 2014/ pa.bpp Tentang Izin Poligami) (UINSI Samarinda, 2016)
This article discusses the considerations of Balikpapan Religious Court judges in giving polygamy permits in case No. 915 / Pdt.G / 2014 / PA.Bpp. In this case the applicant sought permission to marry his partner that he had married earlier not in accordance to state law (Nikah Sirri) 2014. In 2003, the couple was blessed with a son. They then face legal problems to get his birth certificate; and this is one of the reasons the applicant apply for a polygamy permit. Although the application does not meet the provisions of the marriage law in Indonesia about the terms of polygamy (Article 4 (2) Marriage Law No. 1/1974), the judge in the case still gives permission to the applicant . Consideration of the judges are the permission is given because it has greater utility than to simply follow the provisions of the law of marriage: namely legalizing their Nikah Sirri and welfare of the (illegitimate) child. This case shows once again that Religious Court judges are not only glued in the provision of positive law in Indonesia but also delves living law in the community, including here the principles of sharia and fiqh. Keywords : Polygamy in Islam, religious court in Indonesia,